Culinary connections: The mediating role of customer brand co-creation behavior in gastronomic and revisit intentions - Ni Made Purnami; Ni Wayan Mujiati; Ayu Putu Laksmi Danyathi; Uswatun Siwi Kartika Sari; Desak Komang Dea Marcellina Putri Darmada (Innovative Marketing)
The increasing competition in the culinary tourism industry highlights the need for businesses to better understand customer behavior to encourage repeated visits. This study investigates the mediating role of customer brand co-creation behavior in the effect of gastronomic experience on revisit intention among Generation Z café visitors in Bali, Indonesia. Data were collected from 250 respondents via an online survey and analyzed using Partial Least Squares Structural Equation Modeling. The analysis reveals that gastronomic experience has a significant positive impact on revisit intention (β = 0.479, p < 0.05) and customer brand co-creation behavior (β = 0.534, p < 0.05). Additionally, customer brand co-creation behavior positively influences revisit intention (β = 0.380, p < 0.05) and mediates the relationship between gastronomic experience and revisit intention (β = 0.203, p < 0.05). These findings suggest that providing high-quality gastronomic experiences, focusing on food, service, and environment, and encouraging active customer participation in co-creation activities can significantly enhance the likelihood of repeat visits. By fostering deeper customer participation and brand co-creation behavior, businesses can significantly enhance revisit intention, which is essential for long-term success in the competitive culinary tourism sector. These findings contribute to a better understanding of the dynamics between gastronomic experiences, customer brand co-creation behavior, and revisit intentions. AcknowledgementThis research was funded by LPPM Universitas Udayana, Indonesia with contract number: B/255.108/UN14.4.A/PT.01.03/2024.